Phytol: A review of biomedical activities. (November 2018) - Islam, Muhammad Torequl; Ali, Eunüs S.; Uddin, Shaikh J.; Shaw, Subrata; Islam, Md Amirul; Ahmed, Md Iqbal; Chandra Shill, Manik; Karmakar, Utpal Kumar; Yarla, Nagendra Sastry; Khan, Ishaq N.; Billah, Md Morsaline; Pieczynska, Magdalena D.; et al.
Abstract: Phytol (PYT) is a diterpene member of the long-chain unsaturated acyclic alcohols. PYT and some of its derivatives, including phytanic acid (PA), exert a wide range of biological effects. PYT is a valuable essential oil (EO) used as a fragrance and a potential candidate for a broad range of applications in the pharmaceutical and biotechnological industry. There is ample evidence that PA may play a crucial role in the development of pathophysiological states. Focusing on PYT and some of its most relevant derivatives, here we present a systematic review of reported biological activities, along with their underlying mechanism of action. Recent investigations with PYT demonstrated anxiolytic, metabolism-modulating, cytotoxic, antioxidant, autophagy- and apoptosis-inducing, antinociceptive, anti-inflammatory, immune-modulating, and antimicrobial effects. PPARs- and NF-κB-mediated activities are also discussed as mechanisms responsible for some of the bioactivities of PYT. The overall goal of this review is to discuss recent findings pertaining to PYT biological activities and its possible applications.